Audit dan Akreditasi Pendidikan Islam - Irja Eka Putri; Zulfani Sesmiarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Quality transformation and innovation in the digital age have become essential in responding to the rapid pace of technological development, particularly in the field of education. This study aims to analyze the digitization of quality management, the utilization of big data, the implementation of quality information systems, and the development of Islamic education quality in the global era. The study employs a qualitative approach using a literature review (library research) methodology. Data were collected from various scientific journals, books, articles, and academic documents relevant to the research topic. Data analysis was conducted using a descriptive qualitative approach through the stages of data reduction, data presentation, and drawing conclusions. The research results indicate that the digitization of quality management can enhance the effectiveness and efficiency of educational management through faster, integrated, and data-driven work systems. The utilization of big data aids in more accurate evaluation, monitoring, and decision-making processes. Quality information systems play a role in enhancing transparency, accountability, and the sustainable control of educational quality. Meanwhile, Islamic education in the global era is required to integrate technology with Islamic values to remain relevant and competitive. Thus, digital transformation becomes a crucial strategy for improving educational quality and the competitiveness of educational institutions in the modern era.